2016
DOI: 10.1021/acsbiomaterials.6b00144
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Enhancement of Cellular Spheroid Assembly by Acoustically Driven Microcentrifugation

Abstract: S1. Materials and Methods S1.1. Materials Carboxymethyl cellulose sodium salt (M w ~ 90 kDa), tyramine hydrochloride (TYR), N-(3dimethylaminopropyl)-N-ethylcarbodiimide hydrochloride (EDC), N-hydroxysuccinimide (NHS), Tween 20, Triton-X100, deuterium oxide (D 2 O), dialysis tubing (MWCO 124000), and bovine serum albumin (BSA) were obtained from Sigma-Aldrich Pty. Ltd. (Castle Hill, NSW, Australia). Gelatin (M w = 80-140 kDa, pI = 5) and horseradish peroxidase (HRP; 100 units/mg) were obtained from Wako Pure Ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
56
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 58 publications
(58 citation statements)
references
References 82 publications
1
56
0
1
Order By: Relevance
“…Du et al [112] proposed a method to fabricate different micro-scale structures with PEG-based cell laden hydrogels to form MCSs from NIH 3T3 mouse fibroblasts. The [58,59] electric force Jurkat cells [60,61] acoustic force HepG2, BT474 [21,62] rsif.royalsocietypublishing.org J. R. Soc. Interface 14: 20160877 hydrophobic effects drove the 'lock and key' assembly of microgels to form cross-or rod-shaped structures.…”
Section: Micro-mouldingmentioning
confidence: 99%
“…Du et al [112] proposed a method to fabricate different micro-scale structures with PEG-based cell laden hydrogels to form MCSs from NIH 3T3 mouse fibroblasts. The [58,59] electric force Jurkat cells [60,61] acoustic force HepG2, BT474 [21,62] rsif.royalsocietypublishing.org J. R. Soc. Interface 14: 20160877 hydrophobic effects drove the 'lock and key' assembly of microgels to form cross-or rod-shaped structures.…”
Section: Micro-mouldingmentioning
confidence: 99%
“…173 More recently, Alhasan et al used SAW microcentrifugation to assemble cellular spheroids from loose cell aggregates; cellular spheroids are three-dimensional cell structures that more closely mimic cell-cell and cell-matrix interactions found in in vivo environments. 174 Using a clever quick-gelling hydrogel coupling layer, the SAW device was integrated with a microwell plate that contained suspensions of cancer cells (mammary gland carcinoma). As the SAW microcentrifuge concentrated the suspended cells in the center of the microwell, they were able to form tight spheroids without losing cell viability, rapidly producing a platform to study fundamental cell-cell interactions.…”
Section: Saw-integrated Microfluidicsmentioning
confidence: 99%
“…In any case, such on‐chip microcentrifugation flows were subsequently demonstrated as powerful tools to drive micromixing as well as sample and particle preconcentration. In the latter, it was shown to be possible to either induce particle or molecular aggregation into a spot—either at the free surface as a consequence of shear induced migration, or in the bulk due to boundary layer effects on the secondary meriodional recirculation; such an ability to drive particle or solute agglomeration is particularly useful for the separation of red blood cells from plasma, sample/analyte preconcentration, particle sorting/partitioning, cell agglomeration and crystallization, among other applications (alternatively, the opposite effect, i.e., particle/solute dispersion can simply be achieved by increasing the input power to the device). In SAW‐driven cell agglomeration, for example, it was shown that the size of the agglomerates, which could control the size of spheroidal body formation, for example, can be tuned through the SAW power .…”
Section: Active Actuationmentioning
confidence: 99%
“…In the latter, it was shown to be possible to either induce particle or molecular aggregation into a spot—either at the free surface as a consequence of shear induced migration, or in the bulk due to boundary layer effects on the secondary meriodional recirculation; such an ability to drive particle or solute agglomeration is particularly useful for the separation of red blood cells from plasma, sample/analyte preconcentration, particle sorting/partitioning, cell agglomeration and crystallization, among other applications (alternatively, the opposite effect, i.e., particle/solute dispersion can simply be achieved by increasing the input power to the device). In SAW‐driven cell agglomeration, for example, it was shown that the size of the agglomerates, which could control the size of spheroidal body formation, for example, can be tuned through the SAW power . Additionally, the microfluidic centrifugation flows were also demonstrated to be a versatile means for rotating miniature discs on which microfluidic channels can be patterned to carry out a host of different operations and assays—a substantially smaller (a few millimeters as opposed to many centimeters in diameter) and more compact, miniaturized, integrated, and low cost version of the lab‐on‐a‐CD …”
Section: Active Actuationmentioning
confidence: 99%
See 1 more Smart Citation